Change in plasma and erythrocyte thiol levels in children undergoing fasting studies for investigation of hypoglycaemia - Khalid Hussain; Heli Salmi; Risto Lapatto (Pediatric Endocrinology, Diabetes and Metabolism)
Introduction: It is unclear how repeated episodes of HG cause brain injury, but oxidative stress has been suggested to play a role. Non-protein thiols (glutathione, GSH, and cysteine, CYSH) form an important antioxidant defence, and their redox state is dependent on intracellular energy supplies and reducing power which are possibly compromised during low blood glucose concentrations. Aim of study: To study thiol status in children undergoing investigations for hypoglycaemia . We hypothesised that thiol metabolism, dependent on intracellular energy supplies and reducing power, might deteriorate during hypoglycaemic episodes. Material and methods: Seventeen children with suspected hypoglycaemic episodes underwent a diagnostic fast. We measured plasma and erythrocyte GSH and CYSH as well as activities of enzymes related to glutathione metabolism during and after the fast. Results: A positive correlation between plasma glucose and reduced (free) cysteine was observed, but plasma GSH levels did not change significantly. Hypoglycaemia was associated with a rise in erythrocyte total cysteine without changes in erythrocyte GSH. Conclusion: Low blood glucose concentration is associated with changes in thiol status, which compromise the protection against oxidative stress. This further supports the hypothesis of oxidative stress being associated with hypoglycaemia.